An ulnar parametacarpal perforator flap for volar digital soft tissue reconstruction. (October 2020) - Usami, Satoshi; Inami, Kohei; Hirase, Yuichi; Mori, Hiroki
We present outcomes of using a perforator-based ulnar parametacarpal flap in 25 patients for digital pulp defects. These included 17 free transfers to the thumb, index, middle and ring fingers and eight reverse pedicled transfers to the little fingers. This flap includes a dorsal sensory branch of the ulnar nerve, which was sutured to the digital nerve in all transfers. Each flap had one to three reliable perforators (mean 0.44 mm diameter) to the ulnar parametacarpal region and contained at least one perforator within 2 cm proximal to the palmar digital crease. All the 25 flaps survived completely. Twenty-two patients were followed for 15 months (range 12 to 24), and three were lost to follow-up. The mean static and moving two-point discrimination of the flap was 7 mm and 5 mm, respectively. At the donor site, sensory reinnervation was acceptable. We conclude that ulnar parametacarpal perforator flaps offer sensate, thick and glabrous skin for finger pulp repair, all in a single operative field. Level of evidence: IV